Poshpick application / Aiman Ariff Suliman … [et al.] - Suliman, Aiman Ariff; Ahmad Liza, Aina Aniqah; Anuar, Danish Faid; Mohd Rizal, Nur Alia Aqilah; Ibrahim, Nurin Farhah; Mohd Fabli, Siti Nur Nashwa Faqihah (2024)
Brief Description of the Business and Product Concepts: PoshPick emerges as a handy app designed to streamline and simplify the personal shopping process. Its primary goal is to eliminate the need for users to navigate multiple applications or websites to meet their diverse shopping needs. By consolidating various personal shopper services onto one platform, PoshPick aims to provide a seamless and efficient shopping experience across a range of categories, including groceries, clothing, home decor, cosmetics and specialised items. Key features of PoshPick include a diverse array of item categories that personal shoppers can assist in purchasing. Users can easily choose items or brands based on categories, and sample product pictures are provided for easy selection. The app incorporates filter options, allowing users to sort items based on preferences such as price range, category, and rating, ensuring a tailored and personalised shopping experience. All displayed items belong to the chosen brand. The user experience is further enriched through the ability to view personal shopper profiles, including feedback and reviews. PoshPick facilitates live chat interactions with personal shoppers, providing a direct and personalised shopping advisory service. The app includes a secure checkout payment system, allowing users to review their address total amount and receive an invoice order number. Additionally, users can conveniently track their orders through the integrated courier service feature.